1990
DOI: 10.1104/pp.94.2.393
|View full text |Cite
|
Sign up to set email alerts
|

What Is Phloem Unloading?

Abstract: Several studies of phloem unloading have failed to distinguish between transport events occurring at the sieve element/companion cell boundary and subsequent short-distance transport through parenchyma cells. Indirect evidence has been obtained for symplastic unloading in storage and utilization sinks. In other sinks transfer to the apoplast may occur, but not necessarily at the sieve element/companion cell complex, and the evidence for apoplastic phloem unloading is equivocal, as is the role of apoplastic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
51
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 15 publications
1
51
0
Order By: Relevance
“…Studies of [ 14 C]sorbitol unloading suggested that an energy-driven monosaccharide transporter may be functional in phloem unloading. These data provide clear evidence for an apoplasmic phloem unloading pathway in apple fruit and give information on the structural and molecular features involved in this process.The partitioning of sugars in economically important sink organs such as fruits or seeds is governed by several complex physiological processes, including photosynthetic rate, phloem loading in the source leaf, long-distance translocation in the phloem, phloem unloading in sink organs, postphloem transport, and metabolism of imported sugars in sink cells (Oparka, 1990;Patrick, 1997). It is now well accepted that phloem unloading plays a key role in the partitioning of photoassimilate (Fisher and Oparka, 1996;Patrick, 1997;Viola et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of [ 14 C]sorbitol unloading suggested that an energy-driven monosaccharide transporter may be functional in phloem unloading. These data provide clear evidence for an apoplasmic phloem unloading pathway in apple fruit and give information on the structural and molecular features involved in this process.The partitioning of sugars in economically important sink organs such as fruits or seeds is governed by several complex physiological processes, including photosynthetic rate, phloem loading in the source leaf, long-distance translocation in the phloem, phloem unloading in sink organs, postphloem transport, and metabolism of imported sugars in sink cells (Oparka, 1990;Patrick, 1997). It is now well accepted that phloem unloading plays a key role in the partitioning of photoassimilate (Fisher and Oparka, 1996;Patrick, 1997;Viola et al, 2001).…”
mentioning
confidence: 99%
“…It is now well accepted that phloem unloading plays a key role in the partitioning of photoassimilate (Fisher and Oparka, 1996;Patrick, 1997;Viola et al, 2001). The process of phloem unloading has been studied extensively over the last 20 years (for review, see Oparka, 1990;Patrick, 1997;Schulz, 1998) but still remains poorly understood. Elucidation of the cellular pathway of phloem unloading is central to this process, because, to a large extent, the unloading path determines the key transport events responsible for assimilate movement from the sieve elements (SEs) to the recipient sink cells (Fisher and Oparka, 1996;Patrick, 1997).…”
mentioning
confidence: 99%
“…Experimental investigation is complicated by the simultaneous operation of several transport processes (Oparka, 1990). In seeds, these include movement out of the sieve element-companion cell complex (phloem unloading in the strict sense); post-phloem intercellular transport through several distinct tissues; transmembrane movement into the apoplast; uptake by embryonic tissues; and, finally, utilization of assimilates for growth and/or storage.…”
mentioning
confidence: 99%
“…The phenomenon of phloem unloading has been studied extensively over the last decade (for review, see Oparka, 1990;Patrick, 1990Patrick, , 1997Fisher and Oparka, 1996;Schulz, 1998), but remains a poorly understood process. During phloem unloading, assimilates carried by mass flow in the translocation stream exit the sieve element-companion cell (SE-CC) complex (SE unloading;Oparka, 1990;Patrick, 1990) and are subsequently transported through a diverse range of non-phloem tissues (post-phloem transport; Wang and Fisher, 1994;Fisher and Oparka, 1996).…”
mentioning
confidence: 99%
“…During phloem unloading, assimilates carried by mass flow in the translocation stream exit the sieve element-companion cell (SE-CC) complex (SE unloading;Oparka, 1990;Patrick, 1990) and are subsequently transported through a diverse range of non-phloem tissues (post-phloem transport; Wang and Fisher, 1994;Fisher and Oparka, 1996). Evidence from several plant species suggests that a symplastic pathway of SE unloading predominates in many sink tissues, although transfer of solutes to the apoplast may occur at some point along the postphloem pathway (Patrick, 1997).…”
mentioning
confidence: 99%